Pengaruh Current Ratio, Net Profit Margin Dan Kebijakan Dividen Terhadap Harga Saham (Studi Empiris Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Putri Dinda Erika; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2020)
Abstract The purpose of this study was to determine the effect of Current Ratio, Net Profit Margin and Dividend Policy on Share Prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The data analysis technique used is explanatory research using a quantitative approach. The population in this study amounted to 28 companies, the sample selection in this study used a purposive sampling method, the technique of determining the research sample using established considerations. So that a sample of 10 companies was obtained. The data source in this study is the financial statements of food and beverage sub-sector companies in the period 2016 to 2018. And the method used is multiple linear regression. The results showed that partially the Current Ratio variable had a negative and significant effect on the Stock Price, the Net Profit Margin variable had a significant positive effect on the Share Price. While the Dividend Policy has a positive and not significant effect on Stock Prices. Keywords: Current Ratio, Net Profit Margin, Dividend Policy and Stock Price